2007
DOI: 10.1063/1.2812425
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of epitaxial SrHfO3 thin films grown on Si

Abstract: The perovskite SrHfO3 can be a potential candidate among the high-permittivity materials for gate oxide replacement in future metal-oxide semiconductor field-effect transistor technology. Thin films of SrHfO3 were grown by molecular beam epitaxy and compared with SrTiO3 films. Their optical properties were investigated using spectroscopic ellipsometry and analyzed with respect to their structural properties characterized by x-ray diffractometry, atomic force microscopy, and transmission electron microscopy. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
57
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 22 publications
9
57
0
Order By: Relevance
“…Polycrystalline SHO films are reported to have a dielectric constant up to k $ 35, 24,28 leading to an EOT of less than 0.6 nm with a 5 nm film using the ratio of k/3.9. However, other studies have reported lower dielectric constants (k $ 20) for SHO, 26,32 similar to the binary oxide HfO 2 . Finally, SHO has a large band gap of 6.1 eV with favorable conduction band offset ($2.2 eV) and valence band offset ($3.2 eV) with Ge.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Polycrystalline SHO films are reported to have a dielectric constant up to k $ 35, 24,28 leading to an EOT of less than 0.6 nm with a 5 nm film using the ratio of k/3.9. However, other studies have reported lower dielectric constants (k $ 20) for SHO, 26,32 similar to the binary oxide HfO 2 . Finally, SHO has a large band gap of 6.1 eV with favorable conduction band offset ($2.2 eV) and valence band offset ($3.2 eV) with Ge.…”
Section: Introductionmentioning
confidence: 79%
“…Finally, SHO has a large band gap of 6.1 eV with favorable conduction band offset ($2.2 eV) and valence band offset ($3.2 eV) with Ge. 26,34 This is in contrast with Ti-based perovskites, where the Ti 3d states yield negligible conduction band offsets with Si and Ge ($0.1-0.5 eV). 21,22,35 A direct comparison between SHO and STO films on Si (001) has shown a reduction in gate leakage by 4 orders of magnitude for SHO versus STO.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…1 28 and SrHfO 3 . 29,30 The latter two, SrZrO 3 and SrHfO 3 , with pseudocubic lattice constants of 4.101 Å and 4.070 Å at room temperature, respectively, lie off the top of Fig. 1.…”
mentioning
confidence: 95%